The veil after September 11th: the identity and rights of Islamic women - Collares, Valdeli Coelho (2011)
This article intends to clarify and understand the controversial history of wearing the Islamic headscarf, their symbolic power as a group identity and the right or not to use it, either in their home countries, are in other countries. Born from the need to protect the first Muslim women, the veil can not be used to oppress them, as do many non-secular Arab countries, but also can not be banned when their use is adopted as a symbol of political struggle, whether against secular dictatorships Either as an emblem of nationalism. France recently passed a law that prohibits the use of ornament in public places, the justification for such action rests on the embarrassment that such garments and accessories provoke in people who are not Muslim. For a country like France, which holds such strong words like Freedom, Equality and Fraternity, encourages us to question what right are these "freedoms" when that is done is to restrict the freedom of others.